Estrategias didácticas activas para fomentar el pensamiento crítico en los estudiantes de la Carrera de Psicología año 2022 - Lopez Candelario, Lisbeth Samanta (2022)
The purpose of the case study is to determine which active didactic strategies are used in the teaching process of the psychology degree at the Technical University of Babahoyo in the first academic period 2022. This work arises from the concern of seeing how teachers and students they immerse themselves in a current world since the pedagogical transformations at present have been notorious due to the technological incursion. The present investigation used a quantitative approach together with a descriptive scope that allowed to express the analysis and interpretation of the data obtained from the survey applied to the teachers of said career. In addition, the documentary research provided pertinent and necessary information about the benefits and the main active didactic strategies that are used in the teaching-learning process. The results achieved indicate that the application of didactic strategies provides participation between teachers and students, promoting creative spaces that favor the development of critical and reflective thinking in students.